An investigation of the clinical profile and extent of Long QT Syndrome (LQTS) associated with the KCNQ1-A341V mutation in South Africa and with the KCNH2-A1116V mutation in an Italian family and the role that autonomic nervous system (ANS) activity and genetics play in clinical variability - Crotti, Lia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DMed (Medicine. Internal Medicine))--University of Stellenbosch, 2007.